Acting as a change agent: longitudinal effects of a tailored training program aimed at developing the competencies of health and social service professionals - Carrier, Annie; Beaudoin, Michaël; Ethier, Alexandra; Bédard, Denis (Canadian Medical Education Journal, 2025)
Background: We aimed to describe the immediate and medium-term effects of training in the role of change agent (CA) on: 1) the perceived competence to act as a CA; 2) the acquisition of skills required for the role; and 3) the anticipated and actual implementation of CA actions in real-world settings by professionals. Methods: Using a summative evaluation design and a self-administered online questionnaire, we collected data at three time points: before the training, immediately after, and six months later. We analyzed the data using descriptive and inferential statistics. Results: The 39 participants, aged 25 to 44, were mostly women. For both perceived competence to act as a CA and the acquisition of the required skills, the proportion of professionals responding positively increased significantly immediately after the training and decreased six months later. Although professionals intended to act as CAs right after the training, their actions had not materialized within the following six months. Conclusion: Support measures may help sustain the effects of the training in the medium term and encourage real-world implementation of change agent actions.